Efficient Design, Analysis and Implementation of Super-Lift LUO Converter for Standalone PV Applications - Zainab A. Ghafour; Ahmed R. Ajel; Naseer M. Yasin; Noaman Mohammad Noaman (Journal of Techniques)
Positive-output super-lift Luo converters (POSLCs) with low switching losses are the subject of this paper's analysis, design, and regulation. Due to their ability to boost voltage at higher levels, converter switching devices are rarely put under extreme voltage conditions. The input voltage to an active switching device is typically lower than the output voltage. This means that low-quality components are used to build the converter. The proposed conversion can be a good choice in PV micro converter applications requiring high voltage gain. The continuous conduction mode of the converter and its underlying operating principle and steady-state analysis are described. The converter's basic principle is demonstrated by constructing a working hardware prototype, which is tested in the lab. The outcomes demonstrate the benefits of employing an Arduino for voltage control. It has also been found that the converter achieves maximum efficiency of 95.3% at full load. The results were confirmed using MATLAB / Simulink in POSLC design with MPPT which is in agreement with the experimental results.